Blockade of programmed death receptor‐1 signaling restores expression of mostly proinflammatory cytokines in anergic cytomegalovirus‐specific T cells. Issue 1 (26th November 2012) - Dirks, J.; Egli, A.; Sester, U.; Sester, M.; Hirsch, H.H.
Abstract Background Programmed death receptor‐1 (PD‐1) compromises cytomegalovirus (CMV)‐specific T‐cell responses and has been linked to CMV viremia after transplantation. An impaired functional and proliferative capacity of PD‐1‐positive CMV‐specific T cells may be reversed by the antibody‐mediated blockade of PD‐1 signaling. However, knowledge is limited on changes in "cytokinome" expression profiles associated with reversal of functional exhaustion. Methods The "cytokinome" was analyzed by 27‐plex Luminex technology comparing renal transplant recipients with low (n = 5) and high (n = 5) PD‐1 expression on CMV‐specific T cells. The effect of blocking PD‐1 by PD‐ligand (PD‐L) antibodies on restoration of cytokine expression was examined. Results CMV‐specific cytokine release and proliferation was lower in patients with high PD‐1 expression on CMV‐specific T cells. Antibody‐mediated blockade of PD‐L in CMV‐stimulated samples restored expression levels of interleukin (IL)‐1β, IL‐2, IL‐6, IL‐9, IL‐10, granulocyte colony‐stimulating factor, interferon‐γ, macrophage inflammatory protein‐1α, and tumor necrosis factor‐α. By contrast, no profound effect was observed for controls or patients with low PD‐1 expression, or in staphylococcal enterotoxin B‐stimulated cells. Conclusion Taken together, this pilot study provides evidence that a high PD‐1 expression on CMV‐specific T cells actively impairs proliferation and "cytokinome" responses in an antigen‐specific manner. Importantly, blockade of PD‐L restores CMV‐specific T‐cell proliferation and expression of a panel of different proinflammatory and/or type 1 cytokines, suggesting a common but as yet unknown regulatory principle. We conclude that PD‐1 exhaustion is reversible and potentially amenable to therapeutic ex vivo and possibly in vivo manipulation. However, detailed knowledge of the differential effects on the "cytokinome" will be necessary to increase the safety and the efficacy of such manipulations.